Diagnostic inertia in dyslipidaemia: results of a preventative programme in Spain - Palazón-Bru, Antonio (PeerJ, 2015)
Others have analysed the relationship between inadequate behaviour by healthcare professionals in the diagnosis of dyslipidaemia (diagnostic inertia) and the history of cardiovascular risk factors. However, since no study has assessed cardiovascular risk scores as associated factors, we carried out a study to quantify diagnostic inertia in dyslipidaemia and to determine if cardiovascular risk scores are associated with this inertia. In the Valencian Community (Spain), a preventive programme (cardiovascular, gynaecologic and vaccination) was started in 2003 inviting persons aged ≥40 years to undergo a health check-up at their health centre. This cross-sectional study examined persons with no known dyslipidaemia seen during the first six months of the programme (n = 16, 905) but whose total cholesterol (TC) was ≥5.17 mmol/L. Diagnostic inertia was defined as lack of follow-up to confirm/discard the dyslipidaemia diagnosis. Other variables included in the analysis were gender, history of cardiovascular risk factors/cardiovascular disease, counselling (diet/exercise), body mass index (BMI), age, blood pressure, fasting blood glucose and lipids. TC was grouped as ≥/<6.20 mmol/L. In patients without cardiovascular disease and <75/≤65 years (n = 15, 778/13, 597), the REGICOR (REgistre GIroní del COr)/SCORE (Systematic COronary Risk Evaluation) cardiovascular risk functions were used to classify risk (high/low). Inertia was quantified and the adjusted odds ratios calculated from multivariate models. In the overall sample, the rate of diagnostic inertia was 52% (95% CI [51.2–52.7]); associated factors were TC ≥ 6.20 mmol/L, high or “not measured” BMI, hypertension, smoking and higher values of fasting blood glucose, systolic blood pressure and TC. In the REGICOR sample, the rate of diagnostic inertia was 51.9% (95% CI [51.1–52.7]); associated factors were REGICOR high and high or “not measured” BMI. In the SCORE sample the rate of diagnostic inertia was 51.7% (95% CI [50.9–52.5]); associated factors were SCORE high and high or “not measured” BMI. Diagnostic inertia existed in over half the patients and was associated with a greater cardiovascular risk.